Kudus Regency Taxpayer’s Perception on Tax Amnesty Policy - Nika, Restika Noha; Yanto, Heri (Accounting Analysis Journal, 2019)
This study aims to analyze taxpayers? perception in Kudus Regency on tax amnesty policy based on Technology Acceptance Model as main theory and Theory of Planned Behavioral, Theory of Reason Action and perception theory as the supporting theory. There are 63.735 individual taxpayers who are registered in KPP Pratama Kudus as research population. By purposive sampling method, 100 individual taxpayers are obtained as research sample. In addition, this study is examined using path analysis in AMOS 19. Results show that awareness of paying tax has positive and direct effect on intention to utilize tax amnesty, knowledge and understanding of tax amnesty positively affects intention to utilize tax amnesty through awareness of paying tax, and tax sanction has negative impact on intention to utilize tax amnesty through awareness of paying tax. Based on the findings, it can be concluded that taxpayers in Kudus Regency have not acknowledged tax sanction which unable to driven them of having intention to utilize tax amnesty. Thus, future research is recommended to conduct interview towards respondents to gain a more detailed data.